Analisis Pengaruh Atribut Produk Terhadap Keputusan Pembelian Sepeda Motor Merk Happy di Kota Mataram - Octavia, Yusi Faizathul (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2016)
This reaserch is done to analyze the product attribute factors that have inluences toward consumers in the making of purchasing decisions.